2017
DOI: 10.1111/sji.12506
|View full text |Cite
|
Sign up to set email alerts
|

Approach to the Management of Autoimmunity in Primary Immunodeficiency

Abstract: Primary immunodeficiency diseases (PIDs) consist of a genetically heterogeneous group of immune disorders that affect distinct elements of the immune system. PID patients are more prone to infections and non-infectious complications, particularly autoimmunity. The concomitance of immunodeficiency and autoimmunity appears to be paradoxical and leads to difficulty in the management of autoimmune complications in PID patients. Therefore, management of autoimmunity in patients with PID requires special considerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 164 publications
2
40
0
8
Order By: Relevance
“…Moreover, gastrointestinal complications including chronic diarrhea were seen in all patents. Treatment of the autoimmunity, chronic diarrhea and associated colitis is challenging in patients with antibody deficiency (17,18). Uzzan et al (19) reported that Ig supplementation does not significantly effect on the course of non-infectious gastrointestinal disease in CVID patients.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, gastrointestinal complications including chronic diarrhea were seen in all patents. Treatment of the autoimmunity, chronic diarrhea and associated colitis is challenging in patients with antibody deficiency (17,18). Uzzan et al (19) reported that Ig supplementation does not significantly effect on the course of non-infectious gastrointestinal disease in CVID patients.…”
Section: Discussionmentioning
confidence: 99%
“…IgM може ком-пенсувати відсутність IgA в кишечнику шляхом його транспортування зі слизової оболонки в просвіт ки-шечника. Проте повідомляється про зв'язок між SIgAD та целіакією, лямбліозом, вузликовою лімфо-їдною гіперплазією, виразковим колітом, хворобою Крона, злоякісною анемією та аденокарциномою шлунка та кишечника [3,11].…”
Section: клінічна маніфестація селективного дефіциту Igaunclassified
“…Крім того, зв'язок між целіакією та SIgAD може мати генетичну основу, зокрема деякі спільні HLA-гаплотипи, такі як HLA-A1, HLA-Cw7, HLA-B8, HLA-DR3 та HLA-DQ2. Гістопатологія целіакії при SIgAD відрізняється відсутністю IgA-секретуючих плазматичних клітин у зразках біопта-тів кишечника [11,12]. Оскільки целіакія найчастіше виявляється за наявністю IgA-антитіл до вищезгада-них білків (наприклад, трансглутамінази, гліадину та проламіну), у дітей із підозрою на SIgAD пропону-ється ідентифікувати IgG проти деамідованих пеп-тидів гліадину (deamidated gliadin peptide antibody) через високу специфічність для надійної діагности-ки целіакії в пацієнтів із SIgAD (рівень доказовості А) [11].…”
Section: клінічна маніфестація селективного дефіциту Igaunclassified
See 2 more Smart Citations